Manfaat Ekonomi Wisata Alam pada Pemenuhan Pengeluaran Rumah Tangga dan Konservasi Taman Nasional - Asti Istiqomah; Meti Ekayani; . Nuva; Danang Pramudita; Bahroin Idris; . Osmaleli (Jurnal Ilmu Pertanian Indonesia, 2019)
The broadening of Mount Halimun Salak National Park (TNGHS) area is unseparable from the trade off between conservation interest and community’ economic interests. An alternative solution to overcome these problems is an action to conduct natural tourism activities in TNGHS. This action is also expected to encourage the participation of community in preserving national parks. The purpose of this study is to examine economic benefits of nature tourism for maintaining the function of conservation of national parks which at the same time can improve the community’ economy in TNGHS area. The methods used are income analysis which includes ratio of economic benefits from tourism activity to total income and covering of economic benefits from tourism to household expenditure and to conservation fund. The results showed that the economic benefits from natural tourism activity obtained by the community was 66% of the total income and it could also fulfil 91% of household expenditure. In addition, ecotourism activities also generate tourism revenue which is called as PNBP as much as 343% of conservation funds.